CAMOUFLAGE TECHNIQUE WIRELESS MULTIFUNCTIONAL ARMY ROBOT - V, Bharathi; Rao L, Manjunath; B H, Supriya; M, Siddaraju; M R, Bindu (The journal of contemporary issues in business and government, 2021)
Various defense charges are being created today by adopting primitive security to protect the border from intruders. The most important goal of our organization is to blend in, including some extra parameters such as the Wi-Fi component for original-time knowledge administered by the camera on the screen video cassette and the PIR detector to track intruders. The main destination of this project is to change a virtual environment used to detect suspicious and specific places for the user without loss of human lives. The general method of the anti- personal mine detection and identification.